Knowledge production in Malaysia by information professionals for evidence-based librarianship - Mohd Faizal, H.; Ranita, H.S. (2011)

(untitled)
Librarians and information professionals do contribute towards scholarly communication and this paper describes how this is done. A study was carried out with the purpose of analyzing the amount of scholarly communication produced by librarians and information professionals in the MyAIS database. The unit of analysis is a document test collection consisting of 448 articles published from 1982 to 2010. It also reviews the interest pattern of librarians and information professionals in information and knowledge sharing. This study focuses on growth patterns, knowledge accumulation, documentary scatter and knowledge production. Analysis was based on statistical analysis, review and general classification of subjects using the general bibliometric as an instrument of analysis. The results indicate that the amount of scholarly communication produced by librarians and information professionals is not on par with the other social science professionals. In Malaysia, knowledge production among information professionals is far behind. There is lack of contributors who contributes to the creation of knowledge production especially within the library and information science domain. The amount of articles for library and information science as indexed in MyAIS is still very low when compared to the other fields such as Social Science (765), Technology, Engineering (743), Philosophy, Psychology, Religion, Islam (406) and more.